Pequeno leitor - Colosso, Cristiane Otília; Lima , Eliene Xavier de; Babinski , Elizandra Maria Mayer; Domingos , Maria Aparecida; Okazaki , Maria Silvia Guimarães (REVISTA PROGRAMA A UNIÃO FAZ A VIDA_____________________________________________________________________________________________________________, 2021)
>>> ver pdf